2011
DOI: 10.1111/j.1365-2214.2011.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with children who have coeliac disease: a parental perspective

Abstract: Background: This study explores how a child's celiac disease (CD) influences the daily life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 4 publications
2
41
0
4
Order By: Relevance
“…E‐learning, as a tool to increase knowledge and improve disease control, has been reported previously for other chronic diseases . E‐learning is advantageous as it permits asynchronous learning and facilitates education of additional caregivers . With regard to CD, Sainsbury et al showed that an interactive online program improved adult patients' GFD adherence and knowledge compared to patients not receiving the program.…”
Section: Introductionmentioning
confidence: 96%
“…E‐learning, as a tool to increase knowledge and improve disease control, has been reported previously for other chronic diseases . E‐learning is advantageous as it permits asynchronous learning and facilitates education of additional caregivers . With regard to CD, Sainsbury et al showed that an interactive online program improved adult patients' GFD adherence and knowledge compared to patients not receiving the program.…”
Section: Introductionmentioning
confidence: 96%
“…As restrições alimentares constituem fatores de impacto para o portador; portanto, a orientação familiar no processo de enfrentamento dessas mudanças emerge como um dos determinantes favoráveis para o sucesso do tratamento (14).…”
Section: Discussionunclassified
“…Assim, entende-se a mudança de hábitos alimentares como um cuidado de manutenção da vida e como uma mudança na rotina não só da criança, mas também da família (3,14).…”
Section: Discussionunclassified
“…No presente estudo, a transgressão à dieta foi caracterizada em 41,2% das crianças e em 34,5% dos adolescentes que realizaram a determinação do antitransglutaminase tissular, não apresentando diferença estatística entre os grupos. De acordo com os pais, a rápida recuperação dos filhos que seguem a dieta sem glúten é motivo para adequar seus padrões aos novos hábitos alimentares, mas há grande preocupação em relação às escolas e às creches que os filhos frequentam 28 . As transgressões à dieta isenta de glúten ocorrem com maior frequência fora do ambiente domiciliar, ou seja, em decorrência das poucas opções de alimentos sem glúten, as crianças acabam por consumir lanches com glúten 11 .…”
Section: I S C U S S ã Ounclassified
“…A determinação de anticorpos indicativos de atividade da DC e alterações morfológicas na biópsia do intestino delgado são métodos mais invasivos e caros. Diversos artigos discutem a dificuldade dos pacientes no seguimento da dieta 5,6,11,28,29,31,44 . A utilização de uma cozinha experimental, a elaboração de receitas e a divulgação com material informativo sobre glú-ten são fundamentais para esclarecer as principais dúvidas dos pacientes ou de seus responsáveis.…”
Section: Carboidratounclassified